Sequence polymorphism in two novel Plasmodium vivax ookinete surface proteins, Pvs25 and Pvs28, that are malaria transmission-blocking vaccine candidates. - Tsuboi, T. (The Feinstein Institute for Medical Research, 1998)
BACKGROUND: For many malarious regions outside of Africa, development of effective transmission-blocking vaccines will require coverage against both Plasmodium falciparum and P. vivax. Work on P. vivax transmission-blocking vaccines has been hampered by the inability to clone the vaccine candidate genes from this parasite. Materials and METHODS: To search for genes encoding the ookinete surface proteins from P. vivax, the DNA sequences of the eight known proteins in the P25 subfamily (Pfs25, Pgs25, Pys25, Pbs25) and in the P21/28 subfamily (Pfs28, Pgs28, Pys21, Pbs21) of zygote/ookinete surface proteins were aligned. Regions of highest identity were used to design degenerate PCR oligonucleotides. Genomic DNA from the Sal I strain of P. vivax and genomic and splinkerette DNA libraries were used as PCR templates. To characterize the polymorphisms of Pvs25 and Pvs28, these two genes were PCR amplified and the DNA sequences were determined from genomic DNA extracted from patients infected with P. vivax. RESULTS: Analysis of the deduced amino acid sequence of Pvs28 revealed a secretory signal sequence, four epidermal growth factor (EGF)-like domains, six copies of the heptad amino acid repeat (GSGGE/D), and a short hydrophobic region. Because the fourth EGF-like domain has four rather than six cysteines, the gene designated Pvs28 is the presumed homologue of P21/28 subfamily members. Analysis of the deduced amino acid sequence of Pvs25 revealed a similar structure to that of Pvs28. The presence of six rather than four cysteines in the fourth EGF-like domain suggested that Pvs25 is the homologue of P25 subfamily members. Several regions of genetic polymorphisms in Pvs25 and Pvs28 were identified in field isolates of P. vivax. CONCLUSIONS: The genes encoding two ookinete surface proteins, Pvs28 and Pvs25, from P. vivax have been isolated and sequenced. Comparison of the primary structures of Pvs25, Pvs28, Pfs25, and Pfs28 suggest that there are regions of genetic polymorphism in the P25 and P21/28 subfamilies.